The Bezold-Jarisch Reflex and The Inflammatory Response Modulation in Unanesthetized Endotoxemic Rats - Brognara, Fernanda; Castania, Jaci Airton; Ribeiro, Aline Barbosa; Santos-Júnior, Nilton Nascimento; Salgado, Helio Cesar (Frontiers in Physiology, 2021)
Evidence indicates that the activation of the parasympathetic branch of the autonomic nervous system may be effective in treating inflammatory diseases. Previously, we have described that baroreflex activation displays anti-inflammatory properties. Analogous to the baroreflex, the Bezold-Jarisch reflex also promotes parasympathetic activation with simultaneous inhibition of the sympathetic system. Thus, the present study aimed to evaluate whether the activation of the Bezold-Jarisch reflex would also have the ability to reduce inflammation in unanesthetized rats. We used lipopolysaccharide (LPS) injection (5mg/kg, i.p.) to induce systemic inflammation in male Wistar Hannover rats and phenylbiguanide (PBG) administration (5μg/kg, i.v.) to activate the Bezold-Jarisch reflex. Spleen, heart, hypothalamus, and blood samples were collected to determine the levels of cytokines. Compared to baseline, PBG reduced the arterial pressure (115±2 vs. 88±5mmHg) and heart rate (380±7 vs. 114±26bpm), immediately after its administration, confirming the activation of the parasympathetic system and inhibition of the sympathetic system. From the immunological point of view, the activation of the Bezold-Jarisch reflex decreased the plasma levels of TNF (LPS: 775±209 vs. PBG + LPS: 248±30pg/ml) and IL-6 levels in the spleen (LPS: 39±6 vs. PBG + LPS: 24±4pg/mg of tissue). However, it did not change the other cytokines in the plasma or the other tissues evaluated. These findings confirm that the activation of the Bezold-Jarisch reflex can modulate inflammation and support the understanding that the cardiovascular reflexes regulate the immune system.